Ischemic preconditioning increases spinal excitability and voluntary activation during maximal plantar flexion contractions in men - Cruz, Rogério [UNESP]; Tramontin, Artur Ferreira; Oliveira, Anderson Souza; Caputo, Fabrizio; Denadai, Benedito Sérgio [UNESP]; Greco, Camila Coelho [UNESP] (Wiley, 2024)
The enigmatic benefits of acute limb ischemic preconditioning (IP) in enhancing muscle force and exercise performance have intrigued researchers. This study sought to unravel the underlying mechanisms, focusing on increased neural drive and the role of spinal excitability while excluding peripheral factors. Soleus Hoffmann (H)-reflex /M-wave recruitment curves and unpotentiated supramaximal responses were recorded before and after IP or a low-pressure control intervention. Subsequently, the twitch interpolation technique was applied during maximal voluntary contractions to assess conventional parameters of neural output. Following IP, there was an increase in both maximum normalized force and voluntary activation (VA) for the plantar flexor group, with negligible peripheral alterations. Greater benefits were observed in participants with lower VA levels. Despite greater H-reflex gains, soleus volitional (V)-wave and sEMG amplitudes remained unchanged. In conclusion, IP improves muscle force via enhanced neural drive to the muscles. This effect appears associated, at least in part, to reduced presynaptic inhibition and/or increased motoneuron excitability. Furthermore, the magnitude of the benefit is inversely proportional to the skeletal muscle's functional reserve, making it particularly noticeable in under-recruited muscles. These findings have implications for the strategic application of the IP procedure across diverse populations.
Keywords: blood flow restriction; central motor output; compound muscle action potential; intermittent limb ischemia; ischemic conditioning; monosynaptic reflex; peripheral nerve stimulation; surface electromyography